Diversity in Post-Transcriptional Control of Neutrophil Chemoattractant Cytokine Gene Expression - Hamilton, Thomas (2010)
Regulation of neutrophil chemokine gene expression represents an important feature in tissue inflammation. While chemokine gene transcription through the action of NFκB is recognized as an essential component of this process, it is now clear that post-transcriptional mechanisms, particularly the rates of decay of mature cytoplasmic mRNA, provides an essential component of this control. Chemokine and other cytokine mRNA half-life is known to be controlled via adenine-uridine rich sequence motifs localized within 3′ untranslated regions (UTRs), the most common of which contains contains one or more copies of the pentameric AUUUA sequence. In myeloid cells AUUUA sequences confer instability through the action of RNA binding proteins such as tristetraprolin (TTP). The resulting instability can be regulated in response to extracellular stimuli including Toll like receptor ligands that signal to control the function of TTP through pathways involving the activation of p38 MAP kinases. Recent findings indicate that substantial mechanistic diversity is operative in non-myeloid cells in response to alternate pro-inflammatory stimuli such as IL-17. These pathways target distinct instability sequences that do not contain the AUUUA pentamer motif, do not signal through p38 MAPK, and function independently of TTP.